TEACHER EDUCATORS AS BELIEF NAVIGATORS: SHAPING PRE-SERVICE TEACHERS’ PEDAGOGICAL BELIEFS - Zuraimi Zakaria; Nor Tutiaini Ab. Wahid, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This article is grounded in the perspective that pre-service teachers' pedagogical beliefs significantly impact their future classroom practice. It is argued that pre-service teachers have already formed a set of pedagogical beliefs by the time they enrol in teacher education programs. These beliefs are reported to be incongruent with the goals these programs strive to achieve. There is evidence that these pre-existing pedagogical beliefs often remain intact throughout the programs, and in some cases, are even reinforced by them. This is mainly because little effort is made by teacher educators to address or change these beliefs. Studies that investigated teacher change have also explored pedagogical beliefs, as changes in beliefs are a determining factor for changes in practice. The article proposes both general and specific measures that could be undertaken by teacher educators in the design of intervention strategies and programs aimed at changing the pedagogical conceptions and beliefs that pre-service teachers hold. Additionally, the article also addresses the origins and characteristics of these beliefs and their influence on classroom practice and teaching effectiveness.